Improving Literacy Outcomes for Years 5-8 Boys. (Kairaranga, 2011)
This paper reports on a small action research project carried out by a Special Education Needs Coordinator (SENCO) in a small rural, full primary school in New Zealand. It focused on improving the literacy outcomes for Years 5-8 boys in the school by way of a boys’-only writing group. Results show that the boys’-only learning group had a positive impact on the students’ engagement and motivation for learning and improved literacy outcomes.